The Research on Characteristics and Transmission of Traditional Residential Architectural Ornamentation from a Semiotic Perspective :A Case Study of Tongyang Old Street in Chaohu of Anhui Province - Lulu , Ding; Pintong, Sarawuth (Journal of Roi Kaensarn Academi, 2024)
This study aims to examine the characteristics and cultural significance of traditional residential architectural ornamentation in Tongyang Old Street, Chaohu, Anhui Province, from a semiotic perspective. The objective is to identify the aesthetic, functional, and symbolic roles of ornamental patterns and evaluate their influence on modern cultural preservation and innovation. A mixed-methods approach combining literature analysis, field investigations, and case studies was employed. Data collection focused on analyzing ornamental elements, materials, and color schemes, along with their cultural and historical connotations.The results indicate that the architectural ornamentation of Tongyang Old Street exhibits the following notable characteristics: First, material properties, with a primary use of local materials such as blue bricks and black tiles, reflecting a combination of traditional craftsmanship and ecological wisdom. Second, types of ornamentation, encompassing a rich variety of patterns such as intertwining branches and cloud motifs, which serve as carriers of visual aesthetics while embodying profound cultural meanings. Third, symbolic functionality, as many ornamental patterns are inspired by local flora and fauna, conveying the community’s values and aspirations while reflecting philosophical beliefs in the continuity of life and harmony with nature. The ornamentation design achieves a balance between aesthetic appeal and cultural depth in both form and content. The conclusions suggest that these ornamental elements are significant cultural symbols with the potential for innovative applications in modern design, offering valuable insights for the formulation of cultural preservation policies and the integration of traditional aesthetics with contemporary practices.